Kant on Individual Noumena and the Limits of Discursive Understanding - Zanette de Araujo, Rodrigo (Con-Textos Kantianos. International Journal of Philosophy, 2025)
It is relatively uncontroversial among scholars that, according to Kant, we cannot have determinate theoretical cognition of noumena. In this paper I shall argue that Kant’s account of the limits of human understanding allows us to draw a more radical conclusion: the very notion of an individual ‘intelligible being’ lies beyond human comprehension. I further suggest that this claim best conveys Kant’s ban of a positive use of the notion of noumenon. My investigation is guided by a question: Is it possible for concepts to successfully refer to an individual object in absence of sensible intuition? Or, to put it differently, is it possible to single out one or multiple individual noumena (and not mere concepts thereof) falling under a certain concept? I shall argue that, while we cannot exclude this possibility, we cannot comprehend (and thus admit) it either. My hope in this paper is thus to shed further light on Kant’s stance towards noumena.